Convergence CO2 Emission in ASEAN Countries: Augmented Green Solow Model Approach - Gunanto, Edy Yusuf Agung; Wahyu, Tri; Aminata, Jaka; Hayati, Banatul (International Journal of Energy Economics and Policy, 2021)
The purpose of this study is to analyze convergence and factors that affect CO2 growth in ASEAN countries. The model used is the Augmented Green Solow Model developed by Rios & Gianmoena (a2018) based on Brock & Taylor (2004, 2010) which takes into account spatial effects. This study found that during the period 1971-2019, ASEAN countries experienced convergence which was shown to be a significant and negative coefficient of initial CO2, but was fairly slow compared to other studies or regions. Significant variables affect CO2/capita growth in ASEAN countries, namely physical capital investment and trade openness that increases emissions, while human capital significantly reduces emissions. Significant spatial effects occur in initial CO2/capita, physical capital investment, and human capital. The Kyoto Protocol was found to be insignificant in CO2/capita growth in ASEAN countries. Keywords: CO2, Convergence, Green Solow Model JEL Classifications: C23, O13, O44, Q53, Q56 DOI: https://doi.org/10.32479/ijeep.11582